Cuidados de enfermagem a idosos longevos na unidade de pronto socorro: percepção dos atores envolvidos - Silva, Natalina Maria da (2021)
The growth of the eldery population is a world phenomenon, it happens at fast pace, including the age group above 80 years old, in other words, a significant increase of older people. The goal was to analyze the nursing assistance to old people at the Emergency Care Unit at a university hospital from the perspective of actors involved. Also, as specific objectives there were: to characterize the social, economical and clinical profile of the long-lived eldery who remain hospitalized at the ECU of a university hospital, to understand the perception of the long-lived elderly as well as their caregivers, family or not, about the care received at the ECU and knowing the perception of nursing professionals about the care of long-lived elderly at the ECU. The research had an exploratory qualitative research of which 15 eldery people participated, with 80 years or more, 70 caregivers, family or not, and 20 nursing professionals. The data were collected through semi-structured interviews to obtain sociodemographic information and also the Mini-Mental and the Katz scale to assess the cognitive level and functional capacity, respectively, of the old people. Still, open questions were used to understand the perception of the elderly and caregivers about the care provided in the emergency room. The information was analyzed following the steps of thematic analysis and the ethical aspects related to the research were respected. The results showed that older people hospitalized at the emergency room had from 8o to 90 years old, females prevailed, widows, had children, professed the Catholic religion, retired, with elementary education. Among the nursing professionals, the category formed by nursing technicians, female, married, with children and who followed the Catholic religion prevailed. As for caregivers, there was also a predominance of females, married, with children and the degree of kinship with the hospitalized elderly person, with daughters standing out. The content arising from the interviews was grouped into three thematic axes. The first discusses the perception of long-lived elderly people in relation to the care received in the emergency room, they reported that the care provided by nursing professionals was good, full of attention and affection. However, they also expressed that they had no other option but to stay in this space, with inadequate accommodation for hospitalization. The care for long-lived elderly people in the view of nursing professionals, the second thematic axis, showed that they perceived the access of long-lived elderly people to the unit increasing in recent years and associated this fact with the increase in life expectancy of the elderly population. They pointed out that the infrastructure does not provide adequate conditions to care for this audience, especially those with cognitive and functional limitations. Human resources lack qualification for the necessary assistance to all patients who access the service, including elderly people and their families. The care given to the elderly person in the emergency room in the perception of caregivers was configured as the third thematic axis. They understood that the care was adequate and good, but they expressed sadness and concerns when accompanying the elderly person in makeshift accommodations and in the hospital unit corridor. It is noteworthy that the study participants - elderly, nursing professionals and caregivers - share the perception that there is good care provided by the health team, a fact that contributed to alleviate their desires and increase the expectation of improvement. However, they understand that the infrastructure is not equipped/organized to serve long-lived elderly and that there is overcrowding of patients, compromising privacy/individuality, which is not a suitable place for elderly people to be hospitalized for long periods. Thus, it is considered necessary to rethink the work process as well as the infrastructure of the emergency room, inserting facilities, equipment and information technologies as a complementary strategy to provide health care to the elderly, in order to meet the comprehensiveness of care at this level of attention.